Strong Foundation Of Freedom, Justice And Equality In Our Country (On The Example Of The Constitution Of The Republic Of Uzbekistan) (Eurasian Research Bulletin, 2021)
This article interprets the concept of human, as well as concepts such as social security, freedom, justice, equality, on the example of the articles of the Constitution of the Republic of Uzbekistan